Detection of Multi-Drug-Resistance (MDR) Mycobacterium tuberculosis among Suspected Tuberculosis Patients in Bangladesh using Line Probe Assay (Bioresearch Communications, 2022)
Background: Multi-drug resistant (MDR) Tuberculosis (TB) is one of the most significant concerns in tuberculosis control. Genotyping of Mycobacterium tuberculosis helps study evolutionary relationships, its transmission, and molecular epidemiology. The collaborative data from genotyping along with demographic data allows the observation of the current trends of the disease within a population. The molecular tools developed in the past two decades to detect this disease were found to be expensive. Using the Line Probe Assay (LPA) molecular method, it has become simpler to diagnose M. tuberculosis. This study aimed to detect the prevalence of MDR-TB in Bangladesh using LPA.Methods: LPA was used to identify sensitivity or resistance to the antibiotics Isoniazid (INH) and Rifampicin (RIF) (two out of the five first-line TB drugs.).Results: Out of 500 acid-fast smear-positive and LPA-positive sputum samples, the percentages of only RIF, only INH resistant, and resistant to both RIF and INH were 2.2%, 7.6%, and 12.6%, respectively. The majority of the detected MDR-TB cases were from patients within the age range of 21-40 years. This study found the highest number of MDR-TB in the relapse category of patients.Conclusion: LPA can be used successfully to identify MDR-TB prevalence in Bangladesh.Bioresearch Commu. 8(2): 1149-1155, 2022 (July)